ENSIGN WASPS OF SERBIA AND MONTENEGRO (HYMENOPTERA: EVANIOIDEA: EVANIIDAE) (Acta Entomologica Serbica, 2016)
This paper presents the first report on ensign wasp fauna in two central Balkan countries, Serbia and Montenegro. We established the presence of three species  (out of five recorded in Europe): Brachygaster minutus, Prosevania fuscipes and Zeuxevania splendidula, the last based on an old literature report. We briefly discuss the patterns of their distribution and occurrence, in relation to their specific bionomy and the collecting techniques applied.